Efektivitas Program Prukades (Produk Unggulan Kawasan Perdesaan) di Desa Jatibaru Kecamatan Tanjung Bintang Kabupaten Lampung Selatan - Ani Laraswati; Dian Kagungan; Simon Sumanjoyo Hutagalung (Jurnal Administrativa, 2020)
The problem of poverty in rural areas is quite complex and require the intervention all off part together. The Indonesian government has done various effort for diminish destitution in rural area. One of the effort is Prukades Program (Featured Product Of Rural Area). This research is purpose to analysis the effectiveness Prukades Program in Jatibaru Village Tanjung Bintang Sub-District South Lampung Regency as effort poverty breakthrough problem in rural area with apply effectiveness theory. The type of this research is descriptive research with qualitative approach. Data has been collected by means of Interview, observation and documentation. Data analysis has been done with data reduction, data presentation and conclusion drawing. The Effectiveness Prukades Program In Jatibaru Village Tanjung Bintang Sub-District South Lampung Regency is dieficient effective. The indicator effectiveness is achieving goals wich not yet maximally, there was no increase in the quantity and quality of human resources after the socialization and training and the village society was still unable for adapt to technological sophistication. The constraints in carrying out the Prukades Program In Jatibaru Village, Tanjung Bintang Sub-District, South Lampung Regency are the optimal not yet society of participation, the budget of village fund is inadequate and the facilities and infrastructure are inadequate.